DIFFERENCES IN BLOOD GLUCOSE LEVELS BY USING EDTA'S SERUM AND PLASMA WAS EXAMINED IMMEDIATELY AND POSTPONED 2 HOURS AT EFARINA BERASTAGI HOSPITAL - Wahyuni Tarigan , Sri; Frimpong Oppong, Richard; Lubis, Josep; Pakpahan, Romauli; Doortua, Doortua (Universitas Efarina, 2021)
Blood glucose examination in the laboratory is used to determine blood glucose levels in the body. Delay in examination time can cause a decrease in blood glucose levels, so the results obtained do not match the actual body condition. This study aims to determine the difference between blood glucose levels in EDTA plasma samples and serum which were examined immediately and delayed for two hours. This research was conducted using an experimental observation method, namely clinical laboratory observations by measuring blood glucose levels using blood chemistry. The results of examining serum and plasma glucose levels in this study showed that the average value of glucose levels with plasma EDTA which was checked immediately was 99 mg/dl delayed 67.9 mg/dl and serum which was checked immediately was 100.8 mg/dl delayed 100.4 mg /dl.